Estilos de vida en el contexto de la pandemia y periodo de confinamiento, de los estudiantes del Colegio Bachillerato Macará - Novillo Novillo, Luis Fernando (2023)
Lifestyle is defined as a way of living, where individual characteristics interact with living conditions and behavioral patterns, determined by the sociocultural factors that surround it. This study had an observational, analytical and cross-sectional approach where the Fantastic questionnaire was applied to 373 of 512 students, according to the inclusion and exclusion criteria, of the Macará high school in the period October 2021 to July 2022, a process developed with the purpose of knowing the lifestyle of students during confinement in the context of the pandemic; as well as the prevalence of lifestyles in their dimensions nutrition, physical activity, well-being and habits in relation to socioeconomic and biological factors; describe food consumption and eating practices; and finally; determine the relationship between socioeconomic and biological factors with lifestyles. The results were processed in the SPSS program, finding that of the total population, 49.60% (n = 185) of women, specifically 52.01% (n = 194) between the ages of 12 and 15, who completed the tenth year of Basic General Education maintain a balanced diet. Next, 50.40% (n = 188) of women perform minimum physical activity 3 times a week. 88.70% (n = 173) of the participants had adequate weight. The non-parametric chi square tests and Mann Whitney comparison identified no significant statistical relationship between biological, socioeconomic and lifestyle factors. After analyzing the statistical data, it is concluded that women, unlike men, have an adequate lifestyle